Best Practical Paper Award at the 21st European Mediterranean & Middle Eastern Conference on Information Systems (EMCIS 2024) - Lanitis, Andreas (My University, 2026)
The paper ‘Co-designing virtual reality-based solutions to promote the United Nations Sustainable Development Goals’, authored by Kalliopi-Evangelia Stavroulia, Marina Emmanouil, and Andreas Lanitis, has been awarded the Best Practical Paper Award at the 21st European Mediterranean & Middle Eastern Conference on Information Systems “Connecting Minds and Technology to Shape our Digital Future”
Keywords: Sciences